Cytogenetic study of ikan Kelah,Tor sp. (multimedia) - Suhartini Mahmood (2005., 2005)
The cytogenetic study of Ikan Kelah,Tor sp. is multimedia using the combination of graphics,audia,text,animation and real-life video dekivered through the computer.In this multimedia module,its main menu consists of 8 buttons namely the objectives,introduction,cytogenetics,Ikan Kelah,quiz,glossary,bibliography and exit.Various software like Macromedia Authorware 6.5,UleadGIF Animation,Adobe Photoshop 7.0,Adobe Premiere v6.1 and Xara Menu Maker 1.0 were used to make this multimedia module more interesting and interactive.This multimedia module explains about cytogenetics study of ikan kelah.Cytogenetics is a study on chromosome numbers and structures.Chromosomes are stained with Giemsa Stain,then organized in a chart called idiogram.The karyotype is used to define the chromosome size,type and all morphological characteristics.
Project paper (B.S.Cum.Ed.(Hons.)) - Universiti Putra Malaysia, 2005.